Anne Fuchs. Precarious Times: Temporality and History in Modern German Culture. Cornell UP and Cornell University Library, 2019. - Andrea D Bryant (Studies in 20th & 21st Century Literature, 2020)
Review of Anne Fuchs. Precarious Times: Temporality and History in Modern German Culture. Cornell University Press and Cornell University Library, 2019. 322 pp.
Keywords: Eigenzeit; resonance; precariousness; contingency; anthropocene